Biochar derived from citronella and oregano waste residues for removal of organic dyes and soil amendment - Marwa Rammal; Ghenwa Kataya; Adnan Badran; Lara Yazbeck; Chaden Haidar; Khodor Haidar Hassan; Akram Hijazi; Walid Meouche; Mikhael Bechelany; Mohammad H. El-Dakdouki (Current Research in Green and Sustainable Chemistry)
The exponential growth and prominence of the essential oil industry was associated with the generation of large amounts of plant residues which, if not managed properly, present an environmental threat due to their ability to contaminate soil and water systems. This study focuses on the valorization of residues generated from oregano and citronella plants following essential oil extraction. To tackle this challenge, we investigated the potential of biochar of oregano and citronella residues for removing methyl orange dye, a common environmental pollutant, and assessed their phytotoxicity for potential applications as soil amendment. The biochar was produced at different pyrolysis temperatures (300 °C and 400 °C) to study the effect of temperature on the various physicochemical properties of the biochar. Several analytical techniques were used to characterize the generated biochar including Fourier Transform infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), X-ray energy dispersive (EDX) spectroscopy, and X-ray diffraction (XRD) spectroscopy. The efficiency of oregano and citronella biochars produced at different temperatures as soil amendment was evaluated by examining the germination and root development of Lepidium sativum seeds commonly known as garden cress. The control group displayed strong performance with 90–100 % germination and 3.54 cm root length. Oregano biochar obtained by pyrolysis at 300 °C (BOR-300) was toxic to seed growth, while the biochar fabricated at 400 °C (BOR-400) improved germination but fell short of the control. On the other hand, citronella biochar generated at 300 °C (BCR-300) and 400 °C (BCR-400) resulted in better germination compared to BOR, but still lagged behind the control group. Furthermore, our results demonstrated that citronella biochar (BCR) at 400 °C effectively removed 88.8 % of the methyl orange dye. Conversely, the combination of oregano biochar (BOR) and citronella biochar (BCR) at 300 °C did not substantially affect the dye removal efficiency. In summary, applying BOR and BCR produced at 400 °C to soil appears environmentally safe but does not significantly enhance plant growth. These results highlight the critical roles played by biochar type and pyrolysis temperature in shaping the application process.